1990
DOI: 10.1111/j.1365-246x.1990.tb00699.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies of worldwide secular trends in the solar daily geomagnetic variation

Abstract: S U M M A R YSecular changes in the solar geomagnetic variation at 11 observatories with a worldwide distribution have been studied. The secular changes at UK observatories were found to be large. Numerical calculations, details of which are described in this paper, agree in predicting the large changes at UK observatories. The numerical calculations also predict a large secular change in Sq at Hermanus in all elements; this would be expected as the main field at this station shows a large secular change. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 13 publications
1
26
0
Order By: Relevance
“…The Sq amplitude tends to increase significantly during high solar activity. This result is similar to that shown in previous works e.g., Sellek (1980); Schlapp et al (1990). A major cause of the enhancement of the Sq amplitude during high solar activity is thought to be (1) increased height-integrated ionospheric conductivities associated with an increase in the electron density of the ionosphere and (2) increased neutral wind velocity due to enhanced activity of solar tidal waves at the ionospheric height.…”
Section: Elements To Determine the Sq Amplitudesupporting
confidence: 80%
See 1 more Smart Citation
“…The Sq amplitude tends to increase significantly during high solar activity. This result is similar to that shown in previous works e.g., Sellek (1980); Schlapp et al (1990). A major cause of the enhancement of the Sq amplitude during high solar activity is thought to be (1) increased height-integrated ionospheric conductivities associated with an increase in the electron density of the ionosphere and (2) increased neutral wind velocity due to enhanced activity of solar tidal waves at the ionospheric height.…”
Section: Elements To Determine the Sq Amplitudesupporting
confidence: 80%
“…Many investigations of the long-term variation in the Sq amplitude have been performed using long-term geomagnetic field data and several related parameters such as sunspot numbers and the solar F10.7 flux since [Sellek 1980;Schlapp et al 1990;Macmillan and Droujinina 2007;Torta et al 2009;Elias et al 2010]. According to such research, it has been found that the Sq amplitude observed in middle-and low-latitude regions changes with dependence on seasons and solar activity in addition to the activities of solar and lunar tides in the ionosphere.…”
Section: Introductionmentioning
confidence: 99%
“…[21] With relation to Sq trends analyzed by other authors, Schlapp et al [1990] obtained an increase of 3.8 × 10 −5 nT/day (0.014 nT/yr) in the daily amplitude of H (equivalent to the Sq considered here) for Hermanus during a 51 year period Fredericksburg (38.2°N,282.6°E;dashed line),and Hermanus (34.4°S,19.2°E;dotted line). Absolute values have been offset to be comparable to Hermanus's magnetic field by −10,000 nT in the case of Apia and −25,500 nT in the case of Fredericksburg: B(Apia) = plotted value + 10,000 nT; B(Fredericksburg) = plotted value + 25,500 nT.…”
Section: Discussionmentioning
confidence: 99%
“…He found significant secular changes in Sq for Huancayo (12.0°S,284.7°E),Hermanus (34.4°S,19.2°E),and San Juan (18.1°N,293.8°E) that appear to result from changes in the Earth's main magnetic field, and in the case of Huancayo, the trend is also related to movements of the equatorial electrojet. Schlapp et al [1990] studied 11 observatories with a worldwide distribution. They found the largest secular changes in Sq for U.K. stations, and not for Hermanus, which was expected to present the strongest trend in Sq, being the station with the largest secular variation in B.…”
Section: Introductionmentioning
confidence: 99%
“…Sellek (1980) and Schlapp et al (1990) examined the residual Sq amplitude after subtracting the linear fit of the sunspot number to the Sq amplitude. They found significant trends (on the order of 10 −4 nT per day) in the residual data at some stations, but the trends were not always consistent among the stations.…”
Section: Long-term Variationmentioning
confidence: 99%